Level up Learning: A Systematic Review of Gamification in Physical Education - Marcaida, John Louise; Tayag, Dexk Michael; Acebes, Rey; Perez, Carlo Don Daz; Dizon, Ryan; Amaro, Rene; Viray, Raymart; Cabrera, Sergio (Journal of Interdisciplinary Perspectives, 2024)
Gamification is one of the emerging trends in the digital era, which is bound to apply game-based design to a non-game context for engagement, fun, and user enjoyment. Various disciplines and domains increasingly utilize gamification due to its popularity and promising effect. This study is oriented toward systematically analyzing the given literature and studies published in gamification. A systematic review of the literature approach was applied to circumnavigate the methods and techniques used in physical education and the positive and negative implications of the latter. Of 464 related studies, 42 were carefully assessed using the inclusion and exclusion criteria, quality assessment, and data extraction and synthesis. The trend in the use of gamification started in 2010-2020, and in 2019, gamification reached its highest peak. Most relevant studies come from European and American contexts, while few works have been published in Asian, African, and Oceanian contexts. The results of this study attested that in the field of physical education, four domains frequently used gamification, which included physical activity, sports, student engagement, and learning outcomes. Further exploring its beneficial effects could help maximize its usage and popularity.